Geometry impact on fundamental properties of theophylline-containing SLS printed pharmaceutical tablets - Levine, Valerie R.; Katsiotis, Christos S.; Strømme, Maria; Quodbach, Julian; Lindh, Jonas (Frontiers in Drug Delivery, 2024)
Selective Laser Sintering (SLS) has the potential to offer a more accurate alternative to current-practice manipulation of oral dosage forms for pediatric, geriatric, and dysphagia-suffering patient groups. In order to create the best possible dosage forms for these patient groups, an in-depth look into how a dosage forms geometry impacts the overall properties is essential. In this study, the impact of geometry on SLS manufactured oral dosage forms on the tablet’s microstructure, actual-to-theoretical volume, mass deviation, disintegration, and dissolution was investigated. Three different shapes; cylinder, hollow cylinder, and conical frustum with similar surface area (SA), as well as three cylinders with different diameters, were investigated. The results indicate that the geometry has an impact on the mass uniformity, resultant volume, disintegration, and dissolution properties of the tablets. The mass uniformity analysis of the tablets provided the most variation between tablets of different sizes, with more uniformity for tablets with similar SA-to-volume ratio (SA/V). When examining the actual-to-theoretical volume of the tablets, a greater variance between the actual and theoretical volumes for shapes with higher overall SA was observed. The values found are approximately 1.05 for the three differently sized cylinders, 1.23 for the conical frustum, and 1.44 for the hollow cylinder, following this trend. Disintegration data supported a link between SA/V and average disintegration time, observed with the tablet of the highest SA/V disintegrating in 12 s and the tablet with the lowest SA/V disintegrating in 58 s. Dissolution results also indicated a strong dependence on SA/V. Hence, when novel ways to produce oral dosage form tablets become available by additive manufacturing, such as SLS, both geometry and SA/V must be taken into consideration in the tablet design process to ensure appropriate release kinetics and dosing standards.